The effect of tributyltin on human eosinophylic leukemia EoL-1 cells - Sroka, Jolanta (Cell Mol Biol Lett, 2007)
Organotin compounds are chemicals that are widely used in industry and agriculture as plastic stabilizers, catalysts and biocides. Many of them, including tributyltin (TBT), have been detected in human food and, as a consequence, detectable levels have been found in human blood. As organotin compounds were shown to possess immunotoxic activity, we focused our attention on the effect of TBT on the basic determinants of the function of eosinophils, i.e. cell adhesiveness and motility. We used human eosinophylic leukemia EoL-1 cells, a common in vitro cellular model of human eosinophils. Here, we demonstrate that TBT causes a dose-dependent decrease in the viability of EoL-1 cells. When administered at sub-lethal concentrations, TBT significantly decreases the adhesion of EoL-1 cells to human fibroblasts (HSFs) and inhibits their migration on fibroblast surfaces. Since the basic function of eosinophils is to invade inflamed tissues, our results indicate that TBT, and possibly other organotin compounds, may affect major cellular properties involved in the determination of in vivo eosinophil function.